Risks and Challenges of Adopting Electric Vehicles in Smart Cities - Potdar, Vidyasagar; Batool, S.; Krishna, A. (Springer International Publishing, 2018)
Oil prices and increased carbon emissions are two of the key issues affecting mainstream transportation globally. Hence, EVs (Electric VehiclesElectric Vehicles) are becoming popular as they do not depend on oil, and the GHG (Greenhouse Gases) do not contribute to GHG emissions. In fact, their integration with smart grids makes them even more attractive. Although EVEV adoption is becoming widespread, three groups of challenges need to be addressed. These challenges are associated with EV technology adoption, integration of EVs and smart grids, and the supply chain of EV raw materials. Regarding the EV technology adoption, the risks and challenges include EV battery capacity, drivers’ range anxiety, the impact of auxiliary loads, EV drivers’ behavior, EV owners’ unwillingness to participate in the V2GV2G (Vehicle-to-Grid) program, economic barriers to adopting EVs, difficult EV maintenance, EV performance mismatch between the lab and the real world, need for government regulation, lack of charging infrastructure such as not enough charging stations, and expensive batteries. There are additional challenges concerning the integration with the smart grids such as system overload, high-cost investment in V2G technology, load mismatchLoad mismatch, and unmanaged recharging of EV batteries. Finally, there are challenges regarding the consistent supply of the raw materials needed for EVs. This chapter examines these risks and challenges, suggests solutions and provides recommendations for future research.